Price discovery and volatility transmission in Australian REIT cash and futures markets - Lee, Ming-Te; Kuo, Shew-Huei; Lee, Ming-Long; Lee, Chyi Lin (International Journal of Strategic Property Management, 2016)
This study examines the price discovery function and volatility spillovers in australian real estate investment trust (A-REIT) index futures and also investigates the effects of the global fi- nancial crisis (gfc) on these two features. as opposed to the general understanding of the relationship between the cash and the futures markets, the current study finds that the A-REIT cash market led the a-reIt futures market in price discovery and volatility transmission processes before the gfc. However, during the GFC, the two markets interacted bilaterally in terms of information flow, i.e., in- formation flowed in both directions. Furthermore, after the GFC, the futures market followed the cash market again, but less closely. These findings have broad implications for investors in property assets.